Jurnal penelitian pendidikan IPA - Universitas Negeri Surabaya. Jurusan Ilmu Pengetahuan Alam (Universitas Negeri Surabaya, 2016)
Original articles on the latest issues and trends occurring internationally in Science Education.
Keywords: Science : Study and teaching : Indonesia : Periodicals; Science : Study and teaching : Periodicals; Science : Study and teaching; Indonesia